Role of Essential Nutrients as Tools for Reducing Arsenic Hazards in Chilli (Capsicum annuum L.) - Girhepuje, Dipak; Takawale, P. V.; Ugalat, Jayashree; Bandopadhyay, P. K. (International Journal of Bio-resource and Stress Management, 2015)
Capsicum annuum L. was treated with arsenic (As) in pot culture condition to substantiate hazardous effects on growth and biosynthesis of some biomolecules with coexisting effects of essential nutrients namely, manganese (Mn) and phosphate (P). Treatments were applied to plants after 20, 50 and 80 days of transplanting as a soil application. Arsenate (5 mg As kg-1 soil) showed somewhat stimulatory effect on growth and biosynthesis of soluble sugar and soluble protein at the stage of 30 days but at later stages of growth, arsenate was found to be obstructive for fresh and dry shoot weights as well as root weights. Fresh and dry leaf weights and leaf area gradually decreased with increasing concentrations with more doses of As. Arsenic showed significant adverse effect on leaf length and stem diameter of chilli plant. The duration of exposure to arsenate stress was negatively correlated with partitioning of dry matter accumulation. The inhibitory effect of arsenate was less pronounced at the beginning but increased with time. It decreased soluble sugar content, protein content and finally the yield of chilli in the later stages of growth at high concentrations of arsenate. The application of manganese (1 ppm), phosphate (13 mg kg-1 soil) separately and together exhibited significant helpful alterations of all the growth and biochemical characteristics tested under the purview of arsenate treatment alone. In conclusion better growth and yield was observed with the application of manganese and phosphate in chilli seedlings by declining As hazards in arsenic infested soils.